The Effect of Free Cash Flow and Information Asymmetry on Profit Management in Healthcare Sector Companies Listed on the Indonesia Stock Exchange in 2020–2024 - Steffi Rahawarin; Intan Pramesti Dewi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the effect of free cash flow and information asymmetry on earnings management in healthcare companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Earnings management often arises due to conflicts of interest between management and shareholders, which are driven by the availability of free cash flow and information imbalance. This research employs a quantitative method with a causal approach. The population consists of all healthcare companies listed on the IDX, with samples selected using purposive sampling. Secondary data in the form of annual financial statements are used in this study. Data analysis is conducted using multiple linear regression. The results indicate that free cash flow has a negative and significant effect on earnings management, while information asymmetry does not have a significant effect on earnings management. These findings are expected to provide insights for investors and stakeholders in assessing earnings management practices in the healthcare sector.